2014
DOI: 10.1371/journal.pone.0097554
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 (GLP-1) Analog Liraglutide Inhibits Endothelial Cell Inflammation through a Calcium and AMPK Dependent Mechanism

Abstract: Liraglutide is a glucagon-like peptide-1 (GLP-1) mimetic used for the treatment of Type 2 diabetes. Similar to the actions of endogenous GLP-1, liraglutide potentiates the post-prandial release of insulin, inhibits glucagon release and increases satiety. Recent epidemiological studies and clinical trials have suggested that treatment with GLP-1 mimetics may also diminish the risk of cardiovascular disease in diabetic patients. The mechanism responsible for this effect has yet to be determined; however, one pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 57 publications
5
94
0
5
Order By: Relevance
“…Cells from passages 4 to 7 and 90% confluence were used for the experiments after being starved for 3 hours in serum‐free medium. For drug treatment, cultured endothelial cells were incubated with 100 nmol/L liragutide for 15 minutes, which is within the therapeutic range achieved in humans with 1.8 μg/day treatment with liraglutide, and a standard dose used in different types of endothelial cells including human umbilical vein endothelial cells,17 HAECs,24 and cardiac microvascular endothelial cells 25. To investigate the role of GLP‐R1, the GLP‐1R inhibitor Exendin fragment (9–39) (10 nmol/L) was incubated for 30 minutes before liraglutide treatment, as previously described 25…”
Section: Methodsmentioning
confidence: 99%
“…Cells from passages 4 to 7 and 90% confluence were used for the experiments after being starved for 3 hours in serum‐free medium. For drug treatment, cultured endothelial cells were incubated with 100 nmol/L liragutide for 15 minutes, which is within the therapeutic range achieved in humans with 1.8 μg/day treatment with liraglutide, and a standard dose used in different types of endothelial cells including human umbilical vein endothelial cells,17 HAECs,24 and cardiac microvascular endothelial cells 25. To investigate the role of GLP‐R1, the GLP‐1R inhibitor Exendin fragment (9–39) (10 nmol/L) was incubated for 30 minutes before liraglutide treatment, as previously described 25…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that vascular adhesion molecules, including sI-CAM-1 and sVCAM-1, are elevated in patients with diabetes (33). GLP-1 and its analogs downregulate adhesion molecules and nuclear factor-B or activator protein-1 signaling, which are the major redox-sensitive transcriptional pathways responsible for proinflammatory cytokine expression in human vascular endothelial cells and in animal models and diabetic patients (12,16,24,25). In this study, we showed that treatment with exenatide for 12 wk suppressed systemic inflammation in patients with type 2 diabetes by reducing circulating levels of sICAM-1 and sVCAM-1.…”
Section: E953mentioning
confidence: 99%
“…In addition to its established glucose-lowering action, GLP-1 exerts a number of extrapancreatic effects, including improvement of cardiovascular function. Emerging evidence indicates that GLP-1 and its analogs have direct effects on vascular endothelium (6,15,22,24,29,31). Exenatide (a GLP-1 analog) treatment has been demonstrated to induce a significant improvement of brachial artery endothelial function as evaluated by flow-mediated dilation (FMD) in patients with type 2 diabetes (22).…”
mentioning
confidence: 99%
“…Most of the clinical trials, in line with animal studies, have reported a reduction of blood pressure after chronic treatment of GLP-1R agonists [148][149][150][151]. This may be explained, at least in part, by the ability of GLP-1 analogs to upregulate anti-oxidative enzymes and inhibit NFkB-mediated inflammatory signaling on endothelial cells [152,153], and to reduce oxidative stress by suppressing MAPK signaling pathways in peripheral lymphocytes of type 2 diabetic patients [154]. GLP-1-associated improvement of several cardiovascular markers suggests that therapies with GLP-1R agonists may have a positive effect on cardiovascular risk factors in patients with diabetes.…”
Section: How Conventional Diabetic Treatments May Ameliorate Endothelmentioning
confidence: 94%